Viabilidad económica de operar en Colombia taladros petroleros de última generación aplicando buenas prácticas de automatización de procesos utilizados en la aviación (2017)
In this monograph, the economic evaluation of the strategy was made in order to reduce the operational costs generated by the non-productive times, and that, in turn, these times are caused by the human factor in the drilling operations. This strategy consists in implementing the good practices of process automation used in the aviation industry.